Tabagismo e políticas públicas: uma análise sobre a lógica de diferentes estabelecimentos do ramo de entretenimento sobre a proibição de fumar em ambientes fechados - Silveira, Andréa Fernanda (2007)
Tobacco use may be considered a global epidemic and has a great impact on health as well as social, economic and sanitarian consequences. Besides the damage to smoker s health, second hand smoke is very critical to collective health and environment. It is the third leading preventable cause of death in the world. Tobacco control is a public health issue and has been the target of an international framework convention. Among tobacco control policies in Brazil, the 9294/96 law that forbids smoking indoors was chosen to be the purpose of this study. This law is not widely accepted by entertainment establishments (restaurants, bars, fast-food places, cafes, disco houses). Implied is the need to better understand owners and managers rationale concerning to this political issue. In fact, it is important to identify the factors that may influence their decision to adopt this law. For this, an exploratory study was conducted in two phases: a qualitative phase with 11 face-to-face interviews in which the content analysis generated a questionnaire answered by 60 participants in the quantitative phase. To guarantee validity, a panel of 8 experts analyzed the instrument and it was retested by a sub sample of 30 participants. Statistical tests performed showed that 73,3% of participants do not favor the law mentioned above, and that there is no significant difference of opinion among all the segments investigated. Data showed that both political and social factors play a relevant role in this matter. Both variables can not be analyzed apart from each other, as SANDOVAL (2001) and AIRHIHENBUWA (1995) had defended in their theoretical models (political conscientiousness and PEN- 3, respectively). Based on these models, some arguments identified were the law is not enforced, government initiatives are culturally discredited, competition between establishments is great, and owners and managers fear that they would lose business. There is inter- and intra-group favoritism that leads establishments to accept smokers behavior. Data suggests that tobacco control policies for these places must be revisited